UPAYA MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI IPA DENGAN MENGGUNAKAN MODEL SNOWBALL THROWING DI KELAS IV SD NEGERI 050604 BEKIUN - Rita Herlina Br PA; Ester Novitalina Br Tarigan (JURNAL CURERE, 2019)
The study was conducted because there were problems with the students' learning outcomes. Problems faced by students that is less than the maximum use of tools or learning media, so that students lack the spirit of learning and less interested and less active in following the science lesson in the class . To overcome these problems, then conducted research using Snowball Throwing model which aims to know the implementation Learning and improve students' learning outcomes. The type of research is Classroom Action Research. Data collection tools used at the time of the study are observation sheets and tests validated by validators. The study was conducted in 2 cycles and each cycle was held for 2 hours. Based on the research results obtained the observation of teachers and students who expressed good category. The average of student learning outcomes in cycle I and II is 69,27 and 72,5. In cycle I, there are 20 (74,10%) students complete KKM whereas in cycle II there are 24 (88,90%) students complete KKM. Completeness of student learning outcomes has been completed in a classical way. Based on the results of the research it can be stated that the use of Snowball Throwing model can improve student learning outcomes in science lessons of natural resources materials and the results in class IV SD Negeri 050604 Bekiun year 2016/2017 lessons.